A proposed continuing general music education program for the U.P. High School - Nera, Fe Rosario (Capile,)
A continuing general music education program for the UP High School based on the students' musical aptitude, interests, and musical experience, was proposed. An inventory sheet and musical aptitude test was administered to the students. The formulated program made provisions not only for th musically-average and low-achieving, but also for the high-achieving in the form of organized special music classes. Vocal and instrumental classes were also included in the program.